PENGUJIAN KEAMANAN PERANGKAT LUNAK DALAM SOFTWARE DEVELOPMENT LIFE CYCLE - jamiya ranika; Febrina Sari (TEKNOFILE : Jurnal Sistem Informasi, 2023)
ABSTRACTSoftware security testing is an important way to ensure software security. The main goal is to identify security risks develop an effective testing strategy and ensure system security throughout the software development stages. This is done to find weaknesses in the system and check whether the system is protected. Using less secure software can result in information being leaked or used by irresponsible third parties. A better way to improve software security is to incorporate security testing into the SDLC (Software Development Life Cycle) process.